Analisis Waktu Tunggu Pelayanan Resep Pasien BPJS Rawat Jalan di RSUD Bangil - Cikra Ikhda Nur Hamidah Safitri; M. Rizky Arif; Andri Priyoherianto; Lisa Rahmalia Hildiana; Hartono Hartono (Jurnal Rumpun Ilmu Kesehatan, 2024)
Pharmaceutical Services at the Hospital is an integral part of the Hospital's health care system that is patient-oriented, providing Pharmaceutical Preparations Medical Devices, and Medical Materials that are quality and affordable for all levels of society including clinical pharmacy services (Anonymous, 2016) Besed on the Decree of the Minister of Health of the Republic of Indonesia No 179 Menkes/SK/11/2008, the SPM indicator of hospital pharmacy services includes the waiting time for drug services to be a maximum of 30 minutes while the maximum concoction drug is 60 minutes, the absence of medication errors, stalaction customers at least 80% and prescription writing all must refer to the Hospital formulary This study aims to find out the Waiting Time (Respond Time) of Prescription Services for Finished Medicines and drugs mixed with BPJS patients Outpatient in Bangil Hospital. This research is a non-experimental research with descriptive approach, namely the type of research approach to obtain an overview of the state of a group of data based on observations the real thing is, data collection is done in the Outpatient Pharmacy Service at Hangil Hospital, and is carried out for three months. The total mumber of prescription samples erered in the pharmacy installation for three months a 12.587 prescriptions with details of 10,770 prescriptions of JKN BPJS 85.27% 1,808 peral recipes 14 66% and 9 other insurance recipes 0.07% Among the recipe for JKN BPIS obtained during the study were 90.23% of non-concoction recipes and 9.77% of recipe recipes. The results of the study were obtaining results, the number of prescriptions from patients was 85.27% more than prescriptions from general patients 14 66% and other insurance 0.07%. The average waiting time for non-concoction recipe services in 25 minutes, and concoctions are 62 minutes